A 1 kg poodle running right at 3 m/s has an elastic head on collision with a 9 kg basset hound walking left with a velocity of 1 m/s. After the collision the poodle bounces off to the left at 3 m/s. Whats the basset hounds velocity after the collision?
Let m1 is the poodle's weight and V1 is its velocity, m2 is the basset hound's weight and V2 is its velocity before the collision. m1 * V1 - m2 * V2 = - m1 * V1' + m2 * V2' V2' = (m1 * V1 - m2 * V2 + m1 * V1') / m2 V2' = (1 * 3 - 9 * 1 + 1 * 3) / 9 = - 1/3 m/s Answer: 1/3 m/s (directed to the left).